Le Burkina Faso, un producteur de coton face à la mondialisation et à la dépendance économique. Regard sur un Sud - Valérie Hauchart (Cybergeo, 2007)
First cotton-growing country in western Africa, the Burkina Faso choice to build his economic development on production and marketing of this commercial cultivation. Though cotton is exported as unspined product and it is sold facing western competitors who grant financial aid to their producers and supervise stocks, results are concrete. Socio-economic indicators improvement and income provided by cotton prompt the government to produce more and more. Well, intended for exportation production increase generates quality requirements, constraining producers to modernize their farming systems with technical and scientific help of developed countries. New practices popularization, modern tool adoption and farmers training are in the hands of cotton development companies which are partly hold and managed by western shareholders. That is how the Burkina Faso get under developed countries domination.